The microstructure of self-healed PVA ECC under wet and dry cycles - Yu,Jia Huan (2010)
Self-healing of ECC (Engineered Cementitious Composites) subjected to cyclic wetting and drying regimes is investigated in this paper. ECC structures subjected to outdoor environmental conditions such as wind and rain runoff can be simulated by accelerated test method of wetting and drying cycles. Uniaxial tensile tests of ECC M45 and ECC 2.8FA specimen are conducted respectively. It is found that crack width of ECC 2.8FA is around 10 μm with increased amount of fly ash, while the crack width of ECC M45 is around 100 μm. New insights about the microstructure and chemical composition analysis of ECC specimens initially cracked to 2% strain and then self-healed under wet-dry cycles are presented.